Finnair’s “New Silk Road” in the New Millennium: An Analysis of the Construction of Asia and of the Company - Gao, Minghui (fi=Turun yliopisto|en=University of Turku|, 2011)
During the past century, an increasingly diverse world provided us with opportunities for intercultural communication; especially the growth of commerce at all levels from domestic to international has made the combination of the theories of intercultural communication and international business necessary. As one of the main beneficiaries in international business in recent years, companies in airline industries have developed their international market. For instance, Finnair has developed its Asian strategy which responds to the increasing market demand for flights from Europe to Asia in the new millennium. Therefore, the company manages marketing communication in a global environment and becomes a suitable case for studying the theories of intercultural communication in the context of international marketing. Finnair implemented a large number of international advertisements to promote its Asian routes, where Asia has been constructed as a number of exotic destinations. Meanwhile, the company itself as a provider of these destinations has also been constructed contrastively. Thus, this thesis aims at research how Finnair constructs Asia and the company itself in the new millennium, and how these constructions compare with the theories of intercultural communication. This research applied the theories of international marketing, intercultural communication and culture. In order to analyze the collected corpora as Finnair’s international advertisements and its annual reports in the new millennium, the methods of content analysis and discourse analysis have been used in this research. As a result, Finnair has purposefully applied the essentialist approach to intercultural communication and constructed Asia as an exotic “Other” due to the company’s market orientation. Meanwhile, Finnair has also constructed the company itself two identities based on the same approach: as an international airline provider between Europe and Asia, as well as a part of Finnish society. The combination of intercultural communication and international marketing theories, together with the combination of the methods of content analysis and discourse analysis ensure the originality of this paper.